ChemInform Abstract: Importance and Challenges of Electrochemical in Situ Liquid Cell Electron Microscopy for Energy Conversion Research. Issue 45 (October 2016) - Hodnik, Nejc; Dehm, Gerhard; Mayrhofer, Karl J. J.
Abstract: Review: 93 refs.